Implementation of Ecotourism Destination Development Strategies - Taufiq Kurniawan; Muh Gilang Ripani; Siti Danti (Journal on Education, 2023)
The research is located in Ulem-ulem destination of Tetebatu Village. Management of Ulem-ulem forest area and its surroundings has not been optimally carried out, resulting in less effective inter-sectoral coordination. The pattern of natural resources utilization by the community and government has not been fully able to support natural preservation, such as minimum understanding of the concept of ecotourism. In addition, the Tourism Village Management Agency and Tourism Awareness Group of Tetebatu Village do not yet have systematic planning and with integrity related to the development of sustainable ecotourism at Ulem-ulem destination along with waste management that has not yet been implemented. The research employs mixed methods, qualitative and quantitative. To answer the problem formulation regarding development strategy, the researcher employs a qualitative SWOT Matrix approach and questionnaires. The results are presented in four different sub-studies which as a whole will be further discussed.